Development of a French as a foreign language teacher’s “teaching repertoire” in and through retrospective interviews and reflection - Ishikawa, Fumiya (Lingue Culture Mediazioni, 2017)
The retrospective interview carried out as part of foreign language teacher training in France constitutes a complex “polyphonic” (Bakhtin [1975] 1981) situation, where the trainee’s discourse is articulated as a component of “external dialogue” (Vološinov [1929] 1986) with that of the trainer – and sometimes also that of other participating trainees. Each of them refers to, as an element of “internal dialogue” (ibidem), what the trainee said or did in the classroom with and in relation to his/her students as well as what they said or did as action or reaction; that is to say, the classroom interaction in itself can be characterized as an “external dialogue” situation. In focusing on French as a foreign language teacher training, this paper aims to reveal, from a discourse analysis viewpoint, how three elements of retrospective interviews – discourses articulated in relation to each other, the trainee’s retrospective reflection on his/her classroom action and/or his/her students’ (re)actions, and the potential development of his/her ‘teaching repertoire’ – are related to one another.